Assessment of the life quality of patients with multiple sclerosis using the SF-36 scale - N. V. Sturov; M. V. Tardov; E. V. Popova; A. V. Boldin; A. G. Strachuk; Sh. Talapbek k (Сибирский научный медицинский журнал, 2024)
The prevalence of multiple sclerosis (MS) is steadily increasing not only due to rising incidence, but also due to improvements in diagnosis and treatment. Accordingly, there is growing interest in improving the quality of life (QL) of chronic patients, for the assessment of which general scales are used, as well as scales developed specifically for MS. In this work, we analyzed publications devoted to assessing the quality of life of MS patients using the nonspecific SF-36 scale for the period from 2018 to 2023. Data were assessed on all eight scales: physical functioning, role functioning, bodily pain, general health, vitality, social functioning, emotional state and mental health. The usefulness of the SF-36 questionnaire has been shown in the management of patients with MS by a general practitioner for a comprehensive assessment of QL dynamics during treatment and in planning of further treatment and rehabilitation measures. However, the ambiguity of numerous QL studies results in MS obtained using the SF-36 questionnaire requires continued research and improvement of the instrument itself.